Aristophanic Comedy and the Challenge of Democratic Citizenship - Zumbrunnen, John (Book collections on Project MUSE., 2012)
"Aristophanic Comedy and the Challenge of Democratic Citizenship finds in Aristophanes' comedies a complex comic disposition necessary for meeting the fundamental challenge of ordinary citizenship. That challenge, Zumbrunnen argues, emerges from the tension between two democratic impulses: a rebelliousness that resists all attempts to impose any form of institutionalized rule; and an inclination toward collective action taken through institutions of popular rule. Democracy demands that ordinary citizens negotiate the tension between these often conflicting impulses. Aristophanes' comedies rest upon and seek to instill in spectators a complex comic disposition that holds a simple celebration of rebellion in tension with an appreciation for the organized collective action necessary to bring about real change."--Pub. desc.